Ukrainian state building and the views of Gregory Skovoroda on state structure - Tеtiana Boіeva (Cхід, 2013)
Ukraine's integration into European economic and cultural field, building a democratic state, the emergency of new social and economic relations require finding a new national idea. Today our society needs new demands on reforming of all Ukrainian state infrastructure. In the twenty-first century in Ukraine there are two trends of the state - the Ukrainian state on the basis of conservative the Cossack era traditions and state, which it combined with the Russian and Soviet traditions. Based on the analysis of European national ideas, modern Ukrainian idea has to create a common spiritual space and to become a condition for solving the existing political, religious, language problems of cultural processes, to unite all classes, stratas and ethnic groups, which lives on the territory of Ukraine. Ukrainian idea has to be united idea that it should be taken by different political parties, ethnic groups, and representatives of various religious denominations as their own. However, the contradictions between the political forces will remain, but they will exist at the level of the idea implementation ways. Experience of Ukrainian philosophical and legal thought, including G. Skovoroda heritage, discovers a main trend of the modern state development - the gradual Ukrainians` perception of elaborated by progressive political and legal thought achievements and especially those universal values as democracy, law, human rights and freedoms, humane and equitable order. Formation of Ukrainian law state, should ensure the existence of law, protection and guarantee the fundamental rights and freedoms of human being and citizen. However, it should be taken into consideration that law state can not be built by limiting laws adoption. Besides democratic, progressive legislation it is necessary to provide a system of strict observance and fulfillment laws by all participants: state, state bodies, public organizations, officials and citizens. Also the important condition of global events law state creation together the improvement of legislation, is the improvement of legal practice, which, in turn, depends on the legal, professional culture of those who create and use the law.